Power Relationships between Russia, the Crimea and the Ottoman Empire as Reflected in Titulature - Halil Inalcik (Крымское историческое обозрение)
The given articleis a Russian translation of the Turkish historian (Crimean Tatar origin) Halil Inalcik`s work “Power Relationships between Russia, the Crimea, and the Ottoman Empire as Reflected in Titulature”. It analyzes the historical ways of development between Russia, the Crimea and the Ottoman Empire. The author focuses attention on changes of titulature of Russian tsars in the context of changes in mutual power relationships between the states.